Avaliação da zona de risco da raiz mesial de molares inferiores através de tomografia computadorizada multislice com baixa dose de radiação - Harb, Leandro José Corrêa (2016)
The mesial root of Mandibular Molars (MM) of the permanent dentition shows marked mesial-distal flattening and, near to furcation region, a major concavity on its distal surface, determining the so called danger zone (DZ). This is liable to strip perforation on endodontic preparation. Several methodologies reported in literature are used to measure the DZ. The multislice computed tomography (MSCT) allows an evaluation through the 3D reconstruction with high doses of radiations. Until now, no study has analyzed the DZ of MM through the MSCT with low radiation dose. This study evaluated, in vitro, the smaller measure of DZ in the mesial root of MI at levels 1 to 5 millimeters of furcation, with an interval of 1 millimeter between them, using 3D reconstructions obtained by MSCT with low radiation dose (DentalCT protocol - CTdBem). Thirty three MM extracted of humans were used, scanned in CT scanner with subsequently acquisition of 3D image of each tooth though specific software, in which the measures were made. The averages of the smallest measures in millimeters in each level were (first value of the root wall of the mesiobuccal canal) and the second mesiolingual canal): level 1 - N1 (0,79 and 0,83), N2 (0,75 and 0,76), N3 (0,72 and 0,73), N4 (0,75 and 0,74) and N5 (0,82 and 0,73). By the Friedman test (p <0.003), it was confirmed significant difference in root thickness between the 5 levels only for the root wall of mesiolingual canal. By Wilcoxon Test, it was confirmed that the measurement at N1 presented significantly thicker measure than in the remainder 4 levels (p<0,014). In conclusion, 3D reconstructions obtained by MSCT with low radiation dose were proper to the acquisition of virtual images, as well as the analysis of DZ in mesial roots of MM, through a specific program, which were carried out in an efficient and automated way, with no error of demarcation of dental measurable limits, being liable to in vivo and in vitro studies. The results obtained in this study are in accord with the current literature.